MUNAWIR SYADZALI (SEJARAH PEMIKIRAN DAN KONTRIBUSINYA BAGI PERKEMBANGAN PEMIKIRAN ISLAM INDONESIA KONTEMPORER) - Syahril, Sulthan (Universitas Islam Negeri Raden Intan Lampung, 2011)
This article discusses the prominency of Munawir Sjadzali and his thoughts in the vast forest of Indonesia’s contemporary Islamic legal thoughts. He was widely famous for the opinion and thoughts he offered suddenly interested public spotlight. Indeed, controversies over his thoughts took places and inevitably came about. However, the building concept of the Re-actualization of (Law) of Islam which is geneanologically “derivative” of his thought remains a major leap forward ideas for grounding Islamic values of the archipelago on earth, so that Islam is not only known as “Arab”. Islam is a universal religion that is not monopolized by one group of people (Arabs), but each (Muslim) is entitled and has the legitimate right to believe and practice what one believed to be true despite the teachings of Islam they are believing and performing look different from a similar practice in the other hemisphere. Therefore, the reform of tenets (law) of Islam according to the socio-historical background is a sunnatullah. The main points of this paper is focused on introducing the prominency of Munawir Sjadzali and his thoughts, then the explanation expanded to look at the socio-political background in which he gave rise his views. The study concludes with a historical analysis in the light of tarikh tasyri‘ as the first base of Munawir Sjadzali’s full flaged views and thoughts.